The power of self-forgiveness: the dual impact of shame on creativity - Tongtong Ye; Haodong Su (BMC Psychology, 2025)
Abstract While some studies have begun to explore the impact of negative emotions on creativity, the psychological mechanisms through which shame, as a strongly negative emotional experience, affects creativity remain unclear. Furthermore, previous research has predominantly relied on variable-centered methods, potentially masking significant individual differences in shame within populations. Therefore, this study employs an individual-centered latent profile analysis method, grounded in cognitive adjustment model theory and emotion regulation process models, to examine the mediating role of self-forgiveness across different categories of shame. The study surveyed 1023 participants (50.60% male, 49.40% female). The results revealed that latent profile analysis identified five distinct shame groups: Shame-Context Constancy Low, Shame-Context Constancy Moderate, Shame-Context Constancy High, Shame-Context Salience Low, and Shame-Context Salience High. Self-forgiveness played a suppressive mediating role in the Shame-Context Constancy High and Shame-Context Salience High groups, which, in turn, influenced creativity. This study uncovers significant heterogeneity in shame across different groups and elucidates the complex psychological mechanisms through which shame affects creativity: high levels of shame may predict better creative performance, but the lack of self-forgiveness can inhibit the creative benefits derived from shame. These findings provide valuable insights for interventions aimed at enhancing creativity among different shame subgroups.